A consideration of transient response for sensorless model control DC-DC converter - Furukawa, Yudai; Hirotaki, Shota; Watanabe, Shingo; Kurokawa, Fujio; Matsui, Nobumasa; Colak, Ilhami (Intelec, 2015)
The purpose of this paper is to discuss a current prediction algorithm for sensorless model control dc-dc converter. In the proposed method, the sensing resistor for the current detection is eliminated by predicting the output current. The output current is predicted from the equation of the relationship between the output and input voltage in the static state using the duty ratio and the output voltage. The predicted output current is substituted the static model. Two different equations according to the operation mode of the dc-dc converter are used for the current presumption. They should be switched smooth and seamless for the output current prediction.